Customer Satisfaction and the Consumption Function. (5th July 2010) - Ramasamy, Bala; Yeung, Matthew
Abstract : This paper evaluates the extent to which the American Customer Satisfaction Index (ACSI) acts as a determining variable of the US consumption function. Results show that the ACSI is a significant self-predictor of personal consumption expenditure, as well as a potent policy variable even when income and wealth are controlled for.